Implications of the Performance Evaluation of the Job Creation Project - Heesuk Yun (Korea Development Institute (KDI), 2016)
Industrial restructuring and the advent of a 4th industrial revolution are posing challenges that cannot be resolved by conventional methods. However, despite the increasing significance of Korea's Job Creation Project, which aims to foster adaptability and improve labor force mobility, practices remain outdated. Indeed, the project requires extensive reform to properly manage external challenges and to protect the individual not corporations, while stimulating the metabolic process within the economy. - Business entry and exit rate, which remained above 20% until the mid-2000s, have receded to around 10%, and job creation is centered around low-paid and lessskilled occupations, implying a weakening of economic activities. - The Job Creation Project should replace existing regulation-centered protection methods to encourage more activity, while eliminating concerns over change by protecting labor market dropouts. - In other words, the project should serve as a substitute for existing regulations while complementing labor reforms. - Of the target beneficiaries of the employment promotion subsidy, small-sized workplaces with less than five employees account for 54%, but given their constant difficulties of manpower shortages and poor employment conditions, it is almost meaningless to give them a subsidy in the name of employment promotion. - Practices of supporting incompetent companies with various incentives for fear of fewer jobs is no different that intentionally prolonging their survival and thus discriminating potential entrants and hindering the economic metabolic process. - Non-regular workers account for 32.5% of all employees, but only 1.8% were given training program provided by employers. - Market function has not been fully active due to the tight control of quantity and pricing of training programs and the shortage of fiscal support targets. Consequently, of those who completed vocational training for the unemployed, only one of ten is hired for the job he/she was trained for. - The strategy of predicting market trends, planning manpower supply and demand and selecting targets of government support might have worked effectively in the past, but it does not fit in with the present which demands individual creativity and voluntary conversion. - The lack of a unified performance management system is the main reason behind persisting job creation projects that are scattered broadly across ministries. Besides, project performance indicators such as the employment rate and wage are relatively easy to compile but still, a unified system for comparison has not been established. - Of 196 projects handled by 25 ministries, only 64% submitted basic statistics on users within the deadline of fact-finding survey, implying poor management. - Instead of controlling the quantity and fees of vocational training programs and the contents of employment services, the government needs to acknowledge private service providers, while compiling full performance data and linking them to financial upport. - A wide range of incentives must be made available to the disadvantaged who cannot gain employment without government support, and projects that merely support business because they are small or lack funds must be downsized.
Keywords: 330